The Effect of Curcumin on 5-Lipoxygenase (5-LO) Levels in the Hearts of Wistar Rats (Rattus norvegicus) as a Preeclampsia Model - Berliana Noviasih Pertiwi; Lina Zafirah Sukaji; Bambang Rahardjo; Linda Ratna Wati (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2025)
Excessive activation of the 5-lipoxygenase (5-LO) pathway plays a pivotal role in promoting inflammation and endothelial dysfunction, thereby aggravating cardiovascular complications in preeclampsia. Curcumin, a natural polyphenolic compound with well-established anti-inflammatory and antioxidant properties, has been suggested to suppress 5-LO activity. This study aimed to evaluate the effect of curcumin administration on cardiac 5-LO levels in pregnant Wistar rats with an L-NAME?induced preeclampsia model. A true experimental post-test?only control group design was conducted using 25 pregnant Wistar rats divided into five groups, consisting of a negative control, a positive control receiving L-NAME, and three treatment groups administered curcumin at doses of 30, 50, or 100 mg/kg body weight alongside L-NAME. Preeclampsia was induced by L-NAME administration at a dose of 125 mg/kg body weight from gestational day 13 to 19, while curcumin was given orally during the same period. Cardiac 5-LO levels were measured from serum samples using enzyme-linked immunosorbent assay (ELISA) and analyzed using one-way ANOVA followed by Tukey?s post hoc test with a significance level of p < 0.05. The results showed a marked elevation of cardiac 5-LO levels in the positive control group compared to the negative control. Curcumin administration significantly reduced 5-LO levels at all tested doses, with the most pronounced effect observed at 100 mg/kg body weight. Furthermore, a very strong negative correlation was identified between curcumin dose and cardiac 5-LO levels (r = −0.871), indicating a clear dose-dependent response. These findings demonstrate that curcumin effectively suppresses cardiac 5-LO levels in a dose-dependent manner in a preeclampsia rat model and highlight its potential clinical relevance as a natural adjunct therapy for mitigating cardiovascular inflammation and endothelial dysfunction associated with preeclampsiaKeywords: Curcumin, 5-Lipoxygenase, Inflammation, Heart, Preeclampsia